2017
DOI: 10.1007/s00467-017-3725-1
|View full text |Cite|
|
Sign up to set email alerts
|

Rabbit anti-human thymocyte immunoglobulin for the rescue treatment of chronic antibody-mediated rejection after pediatric kidney transplantation

Abstract: In this small series of patients, rATG appears a promising treatment for unresponsive cAMR. Further evaluation, including earlier introduction of rATG, is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…We saw that adjunctive therapy with thymoglobulin failed to achieve a significant improvement in allograft survival rates among some recipients with ABMR. Cihan et al found a significant amelioration of allograft function in 4 of 9 pediatric kidney transplant recipients with chronic ABMR, but larger studies are lacking ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…We saw that adjunctive therapy with thymoglobulin failed to achieve a significant improvement in allograft survival rates among some recipients with ABMR. Cihan et al found a significant amelioration of allograft function in 4 of 9 pediatric kidney transplant recipients with chronic ABMR, but larger studies are lacking ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are plausibly influenced by the absence of PLEX in the first two groups but may suggest noninferiority of ATG to IVIG in vascular rejection. Cihan et al 33 . published a descriptive non‐controlled study with the use of ATG as a rescue treatment in nine chronic AMR in children resistant Steroids/IVIG/Rituximab ± Bortezomib, showing a reversal of graft function degradation in six of the nine cases, with a clear improvement of the graft function in four of them at 9 months after ATG administration.…”
Section: Adjuvant Therapiesmentioning
confidence: 99%